Design of a rectangular microstrip patch antenna at 2.4 GHz with defected ground structure (DGS) effects / Aslinda Zamah Shari - Zamah Shari, Aslinda (2013)
This paper presents the study on the effects of Defected Ground Structure (DGS) on rectangular microstrip patch antenna. The antenna was designed using substrate type of FR-4 with dielectric constant of 4.7, thickness of 1.6 mm, and tangent loss of 0.019. The antenna with and without DGS was analysed to compare the antenna performance between the simulation and the measurement results. The proposed antenna was analysed and simulated at 2.4 GHz for Wireless Local Area Network (WLAN) application. The antenna designed with DGS was 60% more compact than the antenna without DGS. The Computer Simulation Technology (CST) software was used during the simulation result. It was found that by using the DGS method, the size of antenna was reduced.